2016
DOI: 10.1016/j.yexcr.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Tiam1, RhoG and ELMO2/ILK in Rac1-mediated phagocytosis in human trabecular meshwork cells

Abstract: We previously demonstrated that an αvβ5 integrin/FAK- mediated pathway regulated the phagocytic properties of human trabecular meshwork (HTM) cells. Here we demonstrate that this process is mediated by Rac-1 and a previously unreported signaling pathway that utilizes the Tiam1 as well as a novel ILK/RhoG/ELMO2 signaling pathway. Phagocytosis in both a TM-1 cell line and normal HTM cells was mediated by Rac1 and could be significantly decreased by >75% using the Rac1 inhibitor EHop-016. Knockdown of Rac1 in TM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
(69 reference statements)
0
17
0
Order By: Relevance
“… 56 It is well established that TM cells have phagocytic properties. 57 70 Briefly, a single culture of TM cells was established from the B6;129S1-Bambi tm1Jian /J mouse strain by dissecting TM rings from eight eyes. TM rings were placed in collagenase at 37°C for 2 hours.…”
Section: Methodsmentioning
confidence: 99%
“… 56 It is well established that TM cells have phagocytic properties. 57 70 Briefly, a single culture of TM cells was established from the B6;129S1-Bambi tm1Jian /J mouse strain by dissecting TM rings from eight eyes. TM rings were placed in collagenase at 37°C for 2 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Peotter and associates [37] have recently assessed potential roles of Tiam1 and Vav2 in the regulation of Rac1-mediated phagocytosis in human trabecular meshwork [TM] cells. Using pharmacological and molecular biological approaches they demonstrated that αvβ5 integrin/FAK-mediated phogocytosis in these cells is mediated by Rac1.…”
Section: Do Tiam1 and Vav2 Work Together To Facilitate Rac1-mediamentioning
confidence: 99%
“…These studies have also identified ELMO2, RhoG and ILK as upstream regulators of Rac1 activation. Based on these observations, the authors concluded that Tiam1, but not Vav2, plays key regulatory roles in promoting Rac1-mediated phagocytosis in TM cells [37]. …”
Section: Do Tiam1 and Vav2 Work Together To Facilitate Rac1-mediamentioning
confidence: 99%
“…There is an insufficient quantity of pigment in the TM to cause a simple physical outflow obstruction; 7 yet, relatively low amounts of pigment can induce a hypertensive phenotype in ex vivo perfusion cultures. [8][9][10] Additionally, microarray expression analysis suggests a central role for ROCK and IGF-1 8 in the onset of PG.…”
Section: Introductionmentioning
confidence: 99%